Discomposition Redressed - Brandt, Patrick (Narr Francke Attempto Verlag, 2019)
Modern theoretical linguistics lives by the insight that the meanings of complex expressions derive from the meanings of their parts and the way these are composed. However, the currently dominating theories of the syntax-semantics interface hastily relegate important aspects of meaning which cannot readily be aligned with visible structure to empty projecting heads non-reductively (mainstream Generative Grammar) or to the syntactic construction holistically (Construction Grammar). This book develops an alternative, compositional analysis of the hidden aspectual-temporal, modal and comparative meanings of a range of productive constructions of which pseudorefl exive, excessive and directional complement constructions take center stage. Accordingly, a contradiction-inducing hence semantically problematic part of literally coded meaning is locally ignored and systematically realized
9783823392439
Keywords: Syntax-Semantik Schnittstelle; Reparatur; Versteckte Bedeutung; Modalität; Komparative